The Development Science Practicum Module STEM Integratedly on Light Topics with Realistic Approach - Fajri, Nurullina; Putri, Rahmah Evita (Department of Science Education, 2024)
Ideally, science does not only focus on cognitive aspects, but includes attitudes and skills. The implementation of practicum activities aims to improve student skills, cannot be separated from the avalilability of teaching materials that used as a guide in practicum activities. This study purpose to produce a valid and practice science practicum module STEM integratedly on light topics with realistic approach. This research is urgent because produce teaching material that helps teacher and student to assist the practicum activities and can help student to understand the concepts through realistic approach. This is Research and Development (R&D) with three stages of the ADDIE model, namely Analysis; Design; and Development. The result shows the science practicum module STEM integratedly on light topics with realistic approach was valid and practice. Valid and practice means that the teaching material are feasible and easy for use in the learning process. Based on the results, it can be concluded that scince practicum module STEM integratedly on light topics with realistic approach can be used as teaching material that supports practicum activities.